Secure Collection and Analysis of Mobile Broadband Logs - Halldén, Jérémy L.H.P.; Svedlund, Erik B. L. (My University, 2009)
This thesis report contains a description of two successful system developments at the Mobile Broadband Modules department at Ericsson, the first being a system for secure collection of mobile broadband logs; the second being a system for analyzing such logs. Relevant fields studied to solve the different problems imposed by the systems’ requirements, such a field being cryptography, and the solutions chosen for the systems and their software design and implementation are presented. The confidentiality of the log collection was fulfilled by implementing a solution using .NET library classes for the cryptographic algorithms RSA and AES. The log collection itself was realized by using various APIs. The analysis of the logs was made by translating network messages via an algorithm using resource files. High performance was reached by optimizing the string usage and high usability by system prototyping. Sammanfattning Denna examensavhandling innehåller en beskrivning över två framgångsrika systemutvecklingar på Mobile Broadband Modules-avdelningen på Ericsson. Det första är ett system för säker insamling av mobilt bredbandsloggar; det andra ett system för att analysera sådana loggar. Relevanta fält studerade för att lösa de problem förelagda av systemkraven, exempelvis kryptografi, och de valda lösningarna för systemen och deras mjukvarudesign och implementation presenteras. Konfidentialiteten av logginsamlingen åstadkoms genom att implementera en lösning som använder sig av .NET-biblioteksklasser för de kryptografiska algoritmerna RSA och AES. Själva Logginsamlandet genomfördes genom att använda diverse API:er. Logganalyserandet gjordes genom att översätta nätverksmeddelanden via en algoritm som använder sig av resursfiler. Hög prestanda nåddes genom att optimera stränganvändandet och hög användbarhet genom systemprototypning.
Keywords: Programvaruteknik; Software Engineering